The Effect Of Load Frequency Control In Skill Exercises On Some Skill Abilities of Young Soccer Players - Jaefar, Sadiq; Mahdy, Shrooq (Journal of Physical Education, 2019)
The research aimed at identifying the effect of load frequency control in a number of skill abilities of young soccer players. The researchers used the experimental method on (32) soccer player. The training program was applied for (8) weeks with (2) training sessions per week. The data was collected and treated using SPSS. The researchers concluded that controlling load frequency have a positive effect on developing many skill abilities as well as the positive effect of skill exercises on developing many skill abilities. Finally the researchers’ concluded the necessity of using load frequency control to develop skill abilities in soccer.